Pengaruh Pupuk Organik Dan Anorganik Terhadap Sifat Kimia Tanah Dan Pertumbuhan Tanaman Pisang Di Lahan Kering - I Made Mega; I Nyoman Puja (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2018)
This aims of study was to determine the effect of organic and inorganic fertilizers on soil chemical properties and the growth of banana plants on dry land. This research is a factorial experiment with Randomized Block Design (RAK), and three replications. The first factor is the dosage of organic fertilizer that is: B0 (0 kg / plant); B1 (10 kg / plant); B2 (20 kg / plant); while the second treatment is the dose of inorganic fertilizer (NPK) that is: P0 (0 kg / plant); P1 (1 kg / plant); P2 (2 kg / plant). The statistical analysis showed that the treatment of organic and inorganic fertilizer doses did not significantly affect all observed parameters, but in the treatment of organic fertilizers dosage there was an increasing tendency towards: plant height, leaf chlorophyll content, P-available in soil, K-available in soil, and the soil c-organic content, but not significantly different to N-total in soil and number of leaves per plant. The largest plant height was obtained on B1P0 (96.87 cm) treatment, leaf chlorophyll content at B2P2 (72.55 units), P-available in soil at B1P2 treatment (601,12 ppm); K-available in soil at B2P1 treatment (237,67 ppm); and soil Corganic content at B2P0 treatment (4.86%)